Genetic, Physical and Comparative Mapping of the Powdery Mildew Resistance Gene Pm21 Originating from Dasypyrum villosum - He, Huagang; Ji, Yaoyong; Zhu, Shanying; Li, Bin; Zhao, Renhui; Jiang, Zhengning; Bie, Tongde (Frontiers in Plant Science, 2017)
Pm21, originating from wheat wild relative Dasypyrum villosum, confers immunity to all known races of Blumeria graminis f. sp. tritici (Bgt) and has been widely utilized in wheat breeding. However, little is known on the genetic basis of the Pm21 locus. In the present study, four seedling-susceptible D. villosum lines (DvSus-1 ~ DvSus-4) were identified from different natural populations. Based on the collinearity among genomes of Brachypodium distachyon, Oryza and Triticeae, a set of 25 gene-derived markers were developed declaring the polymorphisms between DvRes-1 carrying Pm21 and DvSus-1. Fine genetic mapping of Pm21 was conducted by using an extremely large F2 segregation population derived from the cross DvSus-1/DvRes-1. Then Pm21 was narrowed to a 0.01-cM genetic interval defined by the markers 6VS-08.4b and 6VS-10b. Three DNA markers, including a resistance gene analog (RGA) marker, were confirmed to co-segregate with Pm21. Moreover, based on the susceptible deletion line Y18-S6 induced by EMS treatment conducted on Yangmai 18, Pm21 was physically mapped into a similar interval. Comparative analysis revealed that the orthologous regions of the interval carrying Pm21 were narrowed to a 112.5 kb genomic region harboring 18 genes in Brachypodium, and a 23.2 kb region harboring 2 genes in rice, respectively. This study provides a high-density integrated map of the Pm21 locus, which will contribute to map-based cloning of Pm21.